An Interleaved Broadband Photonic ADC Immune to Channel Mismatches Capable for High-Speed Radar Imaging - Yirong Xu (IEEE, 2019)
A dual channel interleaved broadband subsampling photonic analog-to-digital converter (ADC) immune to channel mismatches capable for high-speed radar imaging is presented. Through modeling as a combination of photonic subsampling front-end and interleaved Nyquist sampling electronic ADC back-end, the mechanism of photonic interleaved subsampling of broadband signal and the appearance of spurious components caused by channel mismatches are explained. The effect of these spurious components on radar detecting is revealed. Through fractional Fourier domain filtering, the spurious components are eliminated, making the SNR of received X-band chirp signal (8–11.9 GHz) improved from 13.26 to 23.88 dB. Thanks to its downsampling and interleaved architecture, the demands of bandwidth, sampling rate, and storage depth for post electronics are all lowered, making it capable for high-speed and mass data receiving. In the experiment, inverse synthetic aperture radar imaging is performed characterized with range and cross range resolution of 4.9 and 7.9 cm. The false target due to the spurious component is distinguished through band-pass filtering in matched fractional Fourier domain.